GUIDELINE FOR THE DEVELOPMENT OF SOCIAL CAPITAL FOR THE LIFELONG LEARNING OF PHU THAI PEOPLE BAN KHAMKANG,KUCHINARAI DISTRICT, KALASIN PROVINCE - Nilkote, Reongwit; Rueangsri, Wongsiri; Sunyamo, Thararat; Lundam , Chatree (Journal of Social Science and Cultural, 2021)
The Objectives of this research article were to 1) study social capital and culture of Phu Thai people, Ban Kham Kang,Lao Yai sub-district, Ku Chi Na Rai district, Kalasin province, and 2) study guidelines for the development lifelong learning education based on social capital. This was a qualitative research that studied data from documents, in-depth interviews, group discussions, participant observations and taking lessons. The key informants were village sages, community leaders and 25 people involved. Data was selecting a specific sample group, learned questions, content analysis and triangulation technique. The research results found that: 1. Social capital and culture of Phu Thai people were included with; 1.1) community history found that they are a group of Thai people whose ancestors were originally from the Black-Dang River Basin for the Socialist Republic of Vietnam and the Lao People’s Democratic Republic like other groups of Thai people 1.2) current area context, the ancestors of the Kham Kung people separated from a large group of Phu Thai people from Kud Sim Na Rai 1.3) social and culture of Phu Thai people who believe in supernatural powers, Hit Sib Song Khong Sib Si custom (ancient custom of Laotian and Thai Isan), Buddhism and 1.4) the potential and social capital that foundation for lifelong learning of the procession and environment dimension. And 2. The guidelines for the development lifelong learning by social capital as a foundation, there were four components: social context, social capital, educational, to supported the life-long learning cycle base on social capital foundation, and the supporting factor was mixing and adjusting to the present, Including knowledge and skills, and ability to created learning cycle.